2012
DOI: 10.12697/akut.2012.18.05
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of warm-up, static and dynamic stretching exercises on biceps brachii muscle function in female basketball players

Abstract: Static and dynamic stretching exercises are often used in sports before competition and training sessions. Recent studies have shown different effects of dynamic and static stretching exercises on physical performance capacity. The aim of the present study was to evaluate the acute effect of warm-up, 30 s static and dynamic stretching exercises on biceps brachii muscle function. Nine athletes were examined twice in different days: after performing static and dynamic stretching exercise. Isometric maximal volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In exploring the effect of warm-up and stretching exercises in sports medicine, Woods et al 16 indicated that appropriate warm-up exercise have physiological benefits (e.g., improves blood flow to muscle tissues in athletes, increases muscle contraction and neurotransmission speed, reduces the risk of sports injury, and enhances flexibility in athletes). In a study to examine the effect of acute biceps warm-up exercises, Veevo et al 17 reported that dynamic warm-up exercises can enhance skeletal muscle contraction in athletes and help athletes perform movements that require power. Effective warm-up exercises before training sessions or games reduce the risk of injury in volleyball players and enhance their performance.…”
mentioning
confidence: 99%
“…In exploring the effect of warm-up and stretching exercises in sports medicine, Woods et al 16 indicated that appropriate warm-up exercise have physiological benefits (e.g., improves blood flow to muscle tissues in athletes, increases muscle contraction and neurotransmission speed, reduces the risk of sports injury, and enhances flexibility in athletes). In a study to examine the effect of acute biceps warm-up exercises, Veevo et al 17 reported that dynamic warm-up exercises can enhance skeletal muscle contraction in athletes and help athletes perform movements that require power. Effective warm-up exercises before training sessions or games reduce the risk of injury in volleyball players and enhance their performance.…”
mentioning
confidence: 99%